Semantic Incompleteness of Liberman et al. (2020)’s Hilbert-style Systems for Term-modal Logics with Equality and Non-rigid Terms - Sawasaki, Takahiro (Bulletin of the Section of Logic, 2025)
In this paper, we prove the semantic incompleteness of some expansions of the Hilbert-style system for the minimal normal term-modal logic with equality and non-rigid terms that were proposed in Liberman et al. (2020) “Dynamic Term-modal Logics for First-order Epistemic Planning.” Term-modal logic is a family of first-order modal logics having term-modal operators indexed with terms in the first-order language. While some first-order formula is valid over the corresponding class of frames in the involved Kripke semantics, it is not provable in those expansions. We show this fact by introducing a non-standard Kripke semantics which makes the meanings of constants and function symbols relative to the meanings of relation symbols combined with them. We also address an incorrect frame correspondence result given in Liberman et al. (2020).